Effect of the waste plastic bottles on properties of asphalt - Kalantar, Z.; Karim, M.R.; Abdel Aziz, M. (2011)
The purpose of this research is to investigate the possibility of using waste Polyethylene Terephthalate as polymer additives in Bituminous binder. The characteristics of PET-modified binder obtained by fix mixing temperature, was investigated. The binders were prepared by mixing the PET in 2%, 4%, 6%, 8% and 10% (by the weight of optimum bitumen) with 80/100 penetration grade bitumen at temperature of 150 ºC. It may be inferred that PET modified bituminous binders provide better resistance against permanent deformations due to their higher G*/sin d and . their higher softening point when compared to conventional binders. Using PET-modified binders also contribute to the recirculation of plastic waste, as well as to the protection of the environment.